High-entropy titanium-aluminum alloy and laser melting deposition preparation method thereof
Through laser melt deposition technology, high entropy alloys and titanium-aluminum alloys are combined to prepare high-entropy-titanium-aluminum alloys with high strength and low density, which solves the problem of limited application of a single high entropy alloy in the aerospace field and realizes the material Efficient preparation and performance improvement.
Patent Information
- Application Number
- CN202411459121.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The application of a single high-entropy alloy in aerospace and other fields is limited by its low strength and high density, making it difficult to meet the needs of lightweight and high strength.
The high-entropy alloy powder and titanium-aluminum alloy powder were placed in the powder feeding barrel respectively by laser melt deposition method to prepare high-entropy-titanium-aluminum alloys, adjust the powder feeding rate of the powder material to change the final composition and improve the material. strength and density reduction.
The prepared high entropy-titanium aluminum alloy has high compression yield strength and microhardness, low density and relative density reach more than 95%, meeting the lightweight requirements, and flexible preparation of different components is achieved by changing the powder feed rate of powder materials. , the efficiency is higher than that of mechanical powder mixing method.
Smart Images

Figure CN119260020A_ABST
Abstract
Description
Technical Field
[0002] The invention relates to the technical field of alloy preparation, and in particular to a high entropy titanium-aluminum alloy and a laser melting deposition preparation method thereof. Background Art
[0003] High entropy alloy is a new concept proposed in recent years. It was originally defined as an alloy composed of 5 or more elements, with each element composition ranging from 5 to 35 at.%. Unlike traditional alloys, high entropy alloys do not have a specific principal element inside. The elements interact with each other to maximize the internal configuration entropy. Therefore, high entropy alloys tend to form solid solution phases rather than ordered intermetallic compounds. The unique structure gives it four major effects that are different from traditional alloys: high entropy effect, hysteresis diffusion effect, lattice distortion effect, and "cocktail" effect. However, the strength of a single high entropy alloy is low and the density is high, which limits its application in aerospace and other fields. Summary of the invention
[0004] The object of the present invention is to provide a high entropy titanium-aluminum alloy and a laser melting deposition preparation method thereof. The high entropy titanium-aluminum alloy provided by the present invention has high strength and low density.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a high entropy titanium-aluminum alloy by laser melting deposition, comprising the following steps: placing a high entropy alloy powder and a titanium-aluminum alloy powder in two powder feeding barrels respectively, performing laser melting deposition on a substrate surface, and obtaining a high entropy titanium-aluminum alloy on the substrate surface; In terms of atomic percentage, the composition of the high entropy alloy powder is Ti3Zr 1.5 VtV 0.25 , the composition of the titanium aluminum alloy powder is Ti-48Al-2Cr-2Nb; The conditions of the laser melting deposition include: a printing power of 1200~1800W, a scanning speed of 8~12mm / s, a laser spot diameter of 3.5~4.0mm, a high entropy alloy powder feeding rate of 6~10g / min, a titanium aluminum alloy powder feeding rate of 0.8~4g / min, an overlap rate of 25~35%, a Z-axis lifting amount of 0.9~1.2mm, a protective gas flow rate of 12~20L / min, and a carrier gas flow rate of 5~8L / min.
[0006] Preferably, the high entropy alloy powder has a spherical shape and a particle size of 50-150 μm.
[0007] Preferably, the titanium aluminum alloy powder is spherical in shape and has a particle size of 20 to 40 μm.
[0008] Preferably, the high entropy alloy powder and the titanium-aluminum alloy powder are placed in front of two powder feeding barrels respectively, and the high entropy alloy powder and the titanium-aluminum alloy powder are dried respectively.
[0009] Preferably, the protective gas is high-purity argon.
[0010] Preferably, the carrier gas is high-purity argon.
[0011] Preferably, the laser melting deposition is performed in a printing chamber, and the oxygen content in the printing chamber is ≤50ppm.
[0012] Preferably, the substrate is a TC4 substrate, a pure Ti substrate or a pure Zr substrate.
[0013] Preferably, before the laser melting deposition, the substrate is polished, cleaned and dried in sequence.
[0014] The present invention provides a high entropy titanium-aluminum alloy prepared by the method of the above scheme, which comprises, in terms of atomic number percentage, Ti: 40-50at.%, Zr: 10-20at.%, Nb: 6-15at.%, V: 6-15at.%, Al: 7-25at.%, Cr: >0 and ≤1.5at.%; The high entropy-titanium aluminum alloy has a compressive yield strength of 1259-1535 MPa, a compressive plasticity of more than 50%, and a microhardness of 357.0-426.8 HV 0.2 , density is 4.834~5.258g / cm 3 , the relative density reaches more than 95%.
[0015] The invention provides a method for preparing a high entropy titanium-aluminum alloy by laser melting deposition, comprising the following steps: placing a high entropy alloy powder and a titanium-aluminum alloy powder in two powder feeding barrels respectively, performing laser melting deposition on a substrate surface, and obtaining a high entropy titanium-aluminum alloy on the substrate surface; the composition of the high entropy alloy powder is Ti3Zr 1.5 VtV 0.25 The composition of the titanium-aluminum alloy powder is Ti-48Al-2Cr-2Nb; the conditions of the laser melting deposition include: a printing power of 1200-1800 W, a scanning speed of 8-12 mm / s, a laser spot diameter of 3.5-4.0 mm, a high entropy alloy powder feeding rate of 6-10 g / min, a titanium-aluminum alloy powder feeding rate of 0.8-4 g / min, an overlap rate of 25-35%, a Z-axis lifting amount of 0.9-1.2 mm, a protective gas flow rate of 12-20 L / min, and a carrier gas flow rate of 5-8 L / min.
[0016] The present invention uses laser melt deposition to prepare high entropy titanium-aluminum alloy. Laser melt deposition has the characteristics of large temperature gradient and fast cooling speed. Therefore, the prepared material often has fine grains, dense structure and excellent mechanical properties. The present invention combines titanium-aluminum alloy with high entropy alloy to improve the overall strength of the alloy. Since the density of titanium-aluminum alloy is low, the overall density of the alloy can be reduced to meet the lightweight requirements.
[0017] The results of the embodiment show that the compressive yield strength of the high entropy-titanium aluminum alloy prepared by the present invention is 1259~1535MPa, the compressive plasticity is greater than 50%, and the microhardness is 357.0~426.8HV 0.2 , density is 4.834~5.258g / cm 3 , the relative density reaches more than 95%.
[0018] The present invention changes the final high entropy-titanium aluminum alloy composition by changing the powder feeding rate of different powder materials. Compared with the laser melting deposition method of mixing powders of different contents and then putting them into a powder feeding bucket, the present invention saves the process of weighing powders and mechanically mixing powders. Moreover, the design of this method is more flexible, and alloys of different compositions can be prepared in batches. Its efficiency is significantly higher than that of the mechanical powder mixing method. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 XRD patterns of high entropy-titanium aluminum alloys with different compositions; Figure 2 Compressive stress-strain curves of high entropy-titanium aluminum alloys with different compositions. DETAILED DESCRIPTION
[0020] The present invention provides a method for preparing a high entropy titanium-aluminum alloy by laser melting deposition, comprising the following steps: placing a high entropy alloy powder and a titanium-aluminum alloy powder in two powder feeding barrels respectively, performing laser melting deposition on a substrate surface, and obtaining a high entropy titanium-aluminum alloy on the substrate surface; In terms of atomic percentage, the composition of the high entropy alloy powder is Ti3Zr 1.5 VtV 0.25 , the composition of the titanium aluminum alloy powder is Ti-48Al-2Cr-2Nb; The conditions of the laser melting deposition include: a printing power of 1200~1800W, a scanning speed of 8~12mm / s, a laser spot diameter of 3.5~4.0mm, a high entropy alloy powder feeding rate of 6~10g / min, a titanium aluminum alloy powder feeding rate of 0.8~4g / min, an overlap rate of 25~35%, a Z-axis lifting amount of 0.9~1.2mm, a protective gas flow rate of 12~20L / min, and a carrier gas flow rate of 5~8L / min.
[0021] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0022] In the present invention, Ti3Zr 1.5 VtV 0.25 The high entropy alloy powder is preferably prepared by rotating electrodes, wherein the electrode running speed is preferably 1-1.5 mm / s, the arc current is preferably 1200-2000 A, and the alloy rod rotation speed is preferably 15000-25000 r / min.
[0023] In the present invention, the high entropy alloy powder is preferably spherical in shape, and the particle size is preferably 50-150 μm; the titanium aluminum alloy powder is preferably spherical in shape, and the particle size is preferably 20-40 μm.
[0024] In the present invention, the high entropy alloy powder and the titanium aluminum alloy powder are placed in front of two powder feeding barrels, respectively, and preferably the high entropy alloy powder and the titanium aluminum alloy powder are dried respectively. In the present invention, the drying temperature is preferably 80° C. and the drying time is preferably 120 min. In the present invention, the drying is preferably carried out in a blast drying oven.
[0025] In the present invention, the substrate is preferably a TC4 substrate, a pure Ti substrate or a pure Zr substrate. Before the laser melting deposition, the present invention preferably further comprises grinding, cleaning and drying the substrate in sequence; the grinding is preferably sandpaper grinding; the cleaning liquid used for cleaning is preferably acetone; the drying temperature is preferably 80°C, and the drying time is preferably 120 minutes.
[0026] In the present invention, the laser melting deposition is preferably performed in a printing chamber, and the oxygen content in the printing chamber is preferably ≤50 ppm.
[0027] In the present invention, the conditions of laser melting deposition include: printing power of 1200~1800W, preferably 1300~1700W, and more preferably 1400~1600W; scanning speed of 8~12mm / s, preferably 9~11mm / s, and more preferably 10mm / s; laser spot diameter of 3.5~4.0mm, preferably 3.6~3.9mm; the high entropy alloy powder feeding rate is 6~10g / min, preferably 7~9g / min; the titanium aluminum alloy powder feeding rate is 0.8~4g / min, preferably 2~3g / min; the overlap rate is 25~35%, preferably 28~32%; the Z-axis lifting amount is 0.9~1.2mm, preferably 1.0~1.1mm; the protective gas flow rate is 12~20L / min, preferably 14~18L / min; the carrier gas flow rate is 5~8L / min, preferably 6~7L / min.
[0028] In the present invention, the protective gas is preferably high-purity argon; the carrier gas is preferably high-purity argon.
[0029] The present invention changes the final high entropy-titanium aluminum alloy composition by changing the powder feeding rate of different powder materials. Compared with the laser melting deposition method of mixing powders of different contents and then putting them into a powder feeding bucket, the present invention saves the process of weighing powders and mechanically mixing powders. Moreover, the design of this method is more flexible, and alloys of different compositions can be prepared in batches. Its efficiency is significantly higher than that of the mechanical powder mixing method.
[0030] In the present invention, the laser melting deposition preferably adopts the YLS-4000-UK fiber laser of German IPG Company, the six-axis linkage robot arm of German KUKA Company, the LH-ZSI-1020-02-201202 laser cladding head of Nanjing Huirui Company, and the CT-1317-01-210903 nozzle of Nanjing Huirui Company.
[0031] The present invention has no special requirements for the implementation process of the laser melting deposition, and the implementation process known in the art can be used. In the embodiment of the present invention, the high entropy alloy powder and the titanium aluminum alloy powder are poured into different powder feeding barrels respectively, the substrate is fixed in the printing cabin, high-purity argon gas is filled into the printing cabin, and the oxygen content in the cabin is detected by an oxygen content meter. After the oxygen content drops below 50ppm and stabilizes for a period of time, the printing work can be started.
[0032] The present invention provides a high entropy titanium-aluminum alloy prepared by the method of the above scheme, which comprises, in terms of atomic number percentage, Ti: 40-50at.%, Zr: 10-20at.%, Nb: 6-15at.%, V: 6-15at.%, Al: 7-25at.%, Cr: >0 and ≤1.5at.%; The high entropy-titanium aluminum alloy has a compressive yield strength of 1259-1535 MPa, a compressive plasticity of more than 50%, and a microhardness of 357.0-426.8 HV 0.2 , density is 4.834~5.258g / cm 3 , the relative density reaches more than 95%.
[0033] The high entropy titanium-aluminum alloy and the laser melting deposition preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0034] The preparation process of high entropy alloy powder in the following examples and comparative examples is as follows: Ti3Zr 1.5 VtV 0.25The high entropy alloy powder was prepared by rotating electrodes, wherein the electrode running speed was 1.4 mm / s, the arc current was 1500 A, and the alloy rod rotation speed was 21000 r / min.
[0035] Example 1 Step 1: Place the high entropy alloy powder and the titanium aluminum alloy powder in a blast drying oven to remove moisture therein. The drying temperature is 80° C. and the drying time is 120 min.
[0036] Step 2: Grind the surface of the TC4 substrate with sandpaper, clean the oil and dust on the surface with acetone, and then dry it in a blast drying oven at a temperature of 80°C for 120 minutes.
[0037] Step 3: Pour the high entropy alloy powder and titanium aluminum alloy powder cooled to room temperature into different powder feeding barrels respectively, fix the substrate in the printing chamber, fill the printing chamber with high-purity argon gas, and use the oxygen content meter to detect the oxygen content in the chamber. After the oxygen content drops below 50ppm and stabilizes for a period of time, you can start printing.
[0038] Step 4: Set the laser melting deposition program through computer software, where the printing power is 1500W, the scanning speed is 10mm / s, the laser spot diameter is 3.85mm, the high entropy alloy powder feeding rate is 9.80g / min, the titanium aluminum alloy feeding rate is 1.09g / min, the overlap rate is 30%, the Z-axis lifting amount is 1.07mm, the protective gas flow rate is 15L / min, and the carrier gas (high-purity argon) flow rate is 6L / min. The robot's calibrator driver is run to complete the entire laser melting deposition process, and the printed sample is cooled to room temperature with the cabin. The mass fraction of titanium aluminum alloy corresponding to this embodiment is 10%.
[0039] Step 5: Use wire cutting to cut the printed material 1 mm above the substrate, clean and polish the workpiece to obtain a typical block sample. The nominal composition of the sample is Ti 45.0 Zr 18.8 Nb 12.8 V 12.5 Al 10.5 Cr 0.3 , the actual composition obtained by scanning the energy spectrum is Ti 46.7 Zr 18.7 Nb 11.2 V 13.4 Al 9.4 Cr 0.6 .
[0040] Example 2 Step 1: Place the high entropy alloy powder and the titanium aluminum alloy powder in a blast drying oven to remove moisture therein. The drying temperature is 80° C. and the drying time is 120 min.
[0041] Step 2: Grind the surface of the TC4 substrate with sandpaper, clean the oil and dust on the surface with acetone, and then dry it in a blast drying oven at a temperature of 80°C for 120 minutes.
[0042] Step 3: Pour the high entropy alloy powder and titanium aluminum alloy powder cooled to room temperature into different powder feeding barrels respectively, fix the substrate in the printing chamber, fill the printing chamber with high-purity argon gas, and use the oxygen content meter to detect the oxygen content in the chamber. After the oxygen content drops below 50ppm and stabilizes for a period of time, you can start printing.
[0043] Step 4: Set the laser melting deposition program through computer software, where the printing power is 1500W, the scanning speed is 10mm / s, the laser spot diameter is 3.85mm, the high entropy alloy powder feeding rate is 8.71g / min, the titanium aluminum alloy feeding rate is 2.18g / min, the overlap rate is 30%, the Z-axis lifting amount is 1.07mm, the protective gas flow rate is 15L / min, and the carrier gas (high-purity argon) flow rate is 6L / min. The robot's calibrator driver is run to complete the entire laser melting deposition process, and the printed sample is cooled to room temperature with the cabin. The mass fraction of titanium aluminum alloy corresponding to this embodiment is 20%.
[0044] Step 5: Use wire cutting to cut the printed material 1 mm above the substrate, clean and polish the workpiece to obtain a typical block sample. The nominal composition of the sample is Ti 45.5 Zr 15.8 Nb 11.1 V 10.5 Al 16.6 Cr 0.6 , the actual composition obtained by scanning the energy spectrum is Ti 47.4 Zr 16.3 Nb 10.1 V 12.0 Al 13.4 Cr 0.8 .
[0045] Example 3 Step 1: Place the high entropy alloy powder and the titanium aluminum alloy powder in a blast drying oven to remove moisture therein. The drying temperature is 80° C. and the drying time is 120 min.
[0046] Step 2: Grind the surface of the TC4 substrate with sandpaper, clean the oil and dust on the surface with acetone, and then dry it in a blast drying oven at a temperature of 80°C for 120 minutes.
[0047] Step 3: Pour the high entropy alloy powder and titanium aluminum alloy powder cooled to room temperature into different powder feeding barrels respectively, fix the substrate in the printing chamber, fill the printing chamber with high-purity argon gas, and use the oxygen content meter to detect the oxygen content in the chamber. After the oxygen content drops below 50ppm and stabilizes for a period of time, you can start printing.
[0048] Step 4: Set the laser melting deposition program through computer software, where the printing power is 1500W, the scanning speed is 10mm / s, the laser spot diameter is 3.85mm, the high entropy alloy powder feeding rate is 7.61g / min, the titanium aluminum alloy feeding rate is 3.28g / min, the overlap rate is 30%, the Z-axis lifting amount is 1.07mm, the protective gas flow rate is 15L / min, and the carrier gas (high-purity argon) flow rate is 6L / min. The robot's calibrator driver is run to complete the entire laser melting deposition process, and the printed sample is cooled to room temperature with the cabin. The mass fraction of titanium aluminum alloy corresponding to this embodiment is 30%.
[0049] Step 5: Use wire cutting to cut the printed material 1 mm above the substrate, clean and polish the workpiece to obtain a typical block sample. The nominal composition of the sample is Ti 45.9 Zr 13.0 Nb 9.5 V 8.7 Al 22.1 Cr 0.8 , the actual composition obtained by scanning the energy spectrum is Ti 47.8 Zr 14.1 Nb 8.8 V 10.5 Al 17.8 Cr 1.0 .
[0050] Comparative Example 1 Step 1: Place the high entropy alloy powder and the titanium aluminum alloy powder in a blast drying oven to remove moisture therein. The drying temperature is 80° C. and the drying time is 120 min.
[0051] Step 2: Grind the surface of the TC4 substrate with sandpaper, clean the oil and dust on the surface with acetone, and then dry it in a blast drying oven at a temperature of 80°C for 120 minutes.
[0052] Step 3: Pour the high entropy alloy powder and titanium aluminum alloy powder cooled to room temperature into different powder feeding barrels respectively, fix the substrate in the printing chamber, fill the printing chamber with high-purity argon gas, and use the oxygen content meter to detect the oxygen content in the chamber. After the oxygen content drops below 50ppm and stabilizes for a period of time, you can start printing.
[0053] Step 4: Set the laser melting deposition program through computer software, where the printing power is 1500W, the scanning speed is 10mm / s, the laser spot diameter is 3.85mm, the high entropy alloy powder feeding rate is 6.53g / min, the titanium aluminum alloy feeding rate is 4.36g / min, the overlap rate is 30%, the Z-axis lifting amount is 1.07mm, the protective gas flow rate is 15L / min, and the carrier gas (high-purity argon) flow rate is 6L / min. The robot's calibrator driver is run to complete the entire laser melting deposition process, and the printed sample is cooled to room temperature with the cabin. The mass fraction of titanium aluminum alloy corresponding to this embodiment is 40%.
[0054] Step 5: Use wire cutting to cut the printed material 1 mm above the substrate, clean and polish the workpiece to obtain a typical block sample. The nominal composition of the sample is Ti 46.3 Zr 10.6 Nb 8.1 V 7.1 Al 26.9 Cr 1.0 , the actual composition obtained by scanning the energy spectrum is Ti 48.6 Zr 11.1 Nb 7.3 V 8.7 Al 23.2 Cr 1.1 .
[0055] Comparative Example 2 Step 1: Place the high entropy alloy powder and the titanium aluminum alloy powder in a blast drying oven to remove moisture therein. The drying temperature is 80° C. and the drying time is 120 min.
[0056] Step 2: Grind the surface of the TC4 substrate with sandpaper, clean the oil and dust on the surface with acetone, and then dry it in a blast drying oven at a temperature of 80°C for 120 minutes.
[0057] Step 3: Pour the high entropy alloy powder and titanium aluminum alloy powder cooled to room temperature into different powder feeding barrels respectively, fix the substrate in the printing chamber, fill the printing chamber with high-purity argon gas, and use the oxygen content meter to detect the oxygen content in the chamber. After the oxygen content drops below 50ppm and stabilizes for a period of time, you can start printing.
[0058] Step 4: Set the laser melting deposition program through computer software, where the printing power is 1500W, the scanning speed is 10mm / s, the laser spot diameter is 3.85mm, the high entropy alloy powder feeding rate is 5.45g / min, the titanium aluminum alloy feeding rate is 5.45g / min, the overlap rate is 30%, the Z-axis lifting amount is 1.07mm, the protective gas flow rate is 15L / min, and the carrier gas (high-purity argon) flow rate is 6L / min. The robot's calibrator driver is run to complete the entire laser melting deposition process, and the printed sample is cooled to room temperature with the cabin. The mass fraction of titanium aluminum alloy corresponding to this embodiment is 50%.
[0059] Step 5: Use wire cutting to cut the printed material 1 mm upward along the substrate, clean and polish the workpiece to obtain a typical block sample.
[0060] Comparative Example 3 Ti3Zr prepared by laser molten deposition 1.5 VtV 0.25 Alloy, the specific steps are as follows: Step 1: Ti3Zr 1.5 VtV 0.25 The high entropy alloy powder is placed in a blast drying oven to remove moisture therein. The drying temperature is 80°C and the drying time is 120 min.
[0061] Step 2: Grind the surface of the TC4 substrate with sandpaper, clean the oil and dust on the surface with acetone, and then dry it in a blast drying oven at a temperature of 80°C for 120 minutes.
[0062] Step 3: Cool the Ti3Zr 1.5 VtV 0.25 The high entropy alloy powder is poured into the powder feeding barrel, the substrate is fixed in the printing chamber, high-purity argon gas is filled into the printing chamber, and the oxygen content in the chamber is tested by an oxygen content meter. After the oxygen content drops below 50ppm and stabilizes for a period of time, printing can begin.
[0063] Step 4: Set the laser melting deposition program through computer software, including printing power 1500W, scanning speed 10mm / s, laser spot diameter 3.85mm, high entropy alloy powder feeding rate 10.89g / min, overlap rate 30%, Z axis lifting amount 1.07mm, protective gas flow rate 15L / min, carrier gas (high purity argon) flow rate 6L / min. The entire laser melting deposition process is completed through the robot's calibrator driver, and the printed sample is cooled to room temperature with the cabin.
[0064] Step 5: Use wire cutting to cut the printed material 1 mm upward along the substrate, clean and polish the workpiece to obtain a typical block sample.
[0065] Structure and performance test: The samples prepared in each embodiment and comparative example were cut into slices with a thickness of 2 mm along a direction perpendicular to the scanning direction for Vickers hardness testing, and cylindrical compression samples with a size of Φ3×4.5 mm were cut along a direction parallel to the deposition direction.
[0066] Comparative Example 2 cracked during the laser melting deposition process and could not be processed into a formed compressed sample, which shows that when the content of titanium aluminum alloy increases to 50%, the brittleness of the high entropy-titanium aluminum alloy increases sharply.
[0067] Figure 1 is the XRD spectrum of high entropy-titanium aluminum alloy with different compositions. Figure 1 It can be seen that each alloy consists of a BCC phase.
[0068] Figure 2 The compression stress-strain curves of high entropy titanium-aluminum alloys with different compositions show that the strength of the material increases with the increase of the titanium-aluminum alloy content. Examples 1 to 3 show good compression plasticity, and no fracture occurs when the strain reaches 50%. As the titanium-aluminum alloy content increases, the plasticity decreases significantly, and comparative example 1 fractures during the compression process, and its compression fracture plasticity is only 30%.
[0069] Table 1 shows the mechanical and density data of high entropy-titanium aluminum alloys with different compositions.
[0070] Table 1 Mechanical and density data of high entropy-titanium aluminum alloys with different compositions
[0071] From the experimental results in Table 1, it can be seen that with the increase of the content of titanium-aluminum alloy, the hardness and compressive yield strength of high entropy-titanium-aluminum alloy gradually increase, which shows that the addition of titanium-aluminum alloy has a certain strengthening effect on the material. In addition, with the increase of the content of titanium-aluminum alloy, the density of the material shows a downward trend. 1.5 VtV 0.25 The density of high entropy alloy in Example 3 decreased by 15.7%, which is of great significance for improving specific strength. The relative density of the materials in the examples and comparative examples is above 95%, which shows that the choice of laser melting deposition process is reasonable.
[0072] Matters not covered by the present invention are known technologies.
[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high entropy titanium-aluminum alloy by laser melting deposition, characterized in that: The following steps are involved: The high entropy alloy powder and the titanium aluminum alloy powder are placed in two powder feeding barrels respectively, and laser melting deposition is performed on the surface of the substrate to obtain the high entropy-titanium aluminum alloy on the surface of the substrate; In terms of atomic percentage, the composition of the high entropy alloy powder is Ti3Zr 1.5 VtV 0.25 , the composition of the titanium aluminum alloy powder is Ti-48Al-2Cr-2Nb; The conditions of the laser melting deposition include: a printing power of 1200~1800W, a scanning speed of 8~12mm / s, a laser spot diameter of 3.5~4.0mm, a high entropy alloy powder feeding rate of 6~10g / min, a titanium aluminum alloy powder feeding rate of 0.8~4g / min, an overlap rate of 25~35%, a Z-axis lifting amount of 0.9~1.2mm, a protective gas flow rate of 12~20L / min, and a carrier gas flow rate of 5~8L / min.
2. The method according to claim 1, characterized in that The high entropy alloy powder has a spherical shape and a particle size of 50-150 μm.
3. The method according to claim 1, characterized in that The titanium aluminum alloy powder has a spherical shape and a particle size of 20 to 40 μm.
4. The method according to any one of claims 1 to 3, characterized in that: The high entropy alloy powder and the titanium aluminum alloy powder are placed in front of two powder feeding barrels respectively, and the high entropy alloy powder and the titanium aluminum alloy powder are dried respectively.
5. The method according to claim 1, characterized in that The protective gas is high-purity argon.
6. The method according to claim 1, characterized in that The carrier gas is high-purity argon.
7. The method according to claim 1, 5 or 6, characterized in that: The laser melting deposition is performed in a printing chamber, and the oxygen content in the printing chamber is ≤50ppm.
8. The method according to claim 1, characterized in that The substrate is a TC4 substrate, a pure Ti substrate or a pure Zr substrate.
9. The method according to claim 1 or 8, characterized in that: Before the laser melting deposition, the substrate is polished, cleaned and dried in sequence.
10. The high entropy titanium-aluminum alloy prepared by the method according to any one of claims 1 to 9, comprising, in terms of atomic percentage, Ti: 40-50 at.%, Zr: 10-20 at.%, Nb: 6-15 at.%, V: 6-15 at.%, Al: 7-25 at.%, Cr: >0 and ≤1.5 at.%; The high entropy-titanium aluminum alloy has a compressive yield strength of 1259-1535 MPa, a compressive plasticity of more than 50%, and a microhardness of 357.0-426.8 HV 0.2 , density is 4.834~5.258g / cm 3 , the relative density reaches more than 95%.
Citation Information
Patent Citations
3D printing micro-area gradient structure high-entropy alloy / titanium and titanium alloy composite material and preparation method and application thereof
CN115627383A
Graphite reinforced high-entropy alloy composite gradient material and preparation method thereof
CN115716133A
Method for improving room-temperature / high-temperature strength and high-temperature durability of 3D printing aluminum alloy
CN116967466A
In-situ strengthened high entropy powder, alloy thereof and method of manufacturing the same
KR1020170123968A
Method for processing ingot and apparatus for processing ingot
KR1020220167223A
Cited By
TiZr-based high-entropy alloy additive manufacturing and heat treatment method
CN119747679A
Selective laser melting homogeneous powder and method for preparing composite material
CN121267200A
High-specific-strength light refractory high-entropy alloy and preparation method and application thereof
CN122406073A